Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This document translates the policy priorities laid out in the Global Policy Agenda (GPA) and the IMFC communique into a work agenda for the Executive Board over the next six to twelve months.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund; Policy Advice; Policy Coherence; Policy; PP